Talent Management and Employee Retention Practices: A Systematic Literature Review and Future Agenda - PANDAY, PRIYANKA; KAUR, Dr. GAGANDEEP (The journal of contemporary issues in business and government, 2021)
Management has been creating a lot of buzz and gaining significant consideration from the practitioners in the last decade. Though, the academic circle is full of literature on existing work related to talent management and employee retention. The objective of this research paper is to systematically present the existing body of knowledge to set the agenda for the future scope of the study. This paper uses the methodology of (Junior et al. 2010; Seuring, 2013).WOS database was used to find the published article between 2011 -2017. The findings revealed that studies are talking in the same line and themes are not diverse in nature. The same idea is being repeated, so there is a need to giving a new perspective and direction to talent management studies. Many conceptual studies are yet not tested and approved for generalization, in such cases, empirical studies can play a major role in setting up further scope of the study. Furthermore, manufacturing industries and developing countries can be in the spotlight in order to fulfill the current gap in talent management and employee retention- related practices.